Antifungal activity of Mentha piperita’s essential oil and alcoholic extracts againts Malassezia furfur - Bravo Torres, Idania; Erazo Yagual, Rosa; García Larreta, Soraya (Revista Universidad de Guayaquil, 2021)
Due to the high incidence of skin diseases such as seborrheic dermatitis and the adverse reactions associated with medications used as treatment for these disorders, the objective of this study is to evaluate the antifungal activity of alcoholic extracts and essential oil from the leaves of Mentha piperita against the fungus Malassezia furfur. The extraction procedures consisted of maceration processes, drying at low temperatures and filtration of the 70% alcoholic extract obtained from the leaves, as well as the steam drag method where once the essence was condensed, it was collected and separated from the aqueous fraction to obtain essential oil. The aura inhibitors of the microorganism were determined by Kirby Bauer disc diffusion methodology, using a pure strain of Malassezia furfur ATCC that was seeded in a homogeneous suspension plate of the microorganism’s lyophilisate, in Sabouraud Dextrose Agar fortified with 10% extra virgin olive over a 7 days period, in incubation at 30 ° C. The determination of the antifungal activity, dilutions was made at different concentrations both for essential oil and the alcoholic extract, the results were established by degrees of sensitivity. These results indicated that the essential oils of Mentha piperita showed bigger aura inhibitors against the microorganism M. furfur, the main cause of diseases such as seborrheic dermatitis, in comparison with the alcoholic extracts.